Climate change and water resources in Algeria: Vulnerability, impact and adaptation strategy - Touitou Mohammed; Abul Quasem Al-Amin (Economic and Environmental Studies (E&ES), 2018)
The climate changes going on for a long time now have ceased to be a scientific curiosity. They constitute the major environmental question which dominates our time and pose the major challenge to environmental organizations of control. Water is one of the most important raw materials in Algeria. Because of its importance, it is essential to know its vulnerability with the climate changes. In Algeria, the vulnerability due to the climate changes is expressed through several aspects: demographic explosion, probable reduction in the water run-offs, scarcity of the resources, the degradation of the hydraulic infrastructures, threats to wetlands, etc. In the face of this situation, Algeria has taken quantitative and qualitative adaptive measures within the framework of durable management of this invaluable resource for the future.
Keywords: Q54; Q25; 330; climate changes; water; vulnerability; strategy of adaptation; Algeria